ELISA reader does not interfere by mobile phone radiofrequency radiation - Seyyed Mohammad Javad Mortazavi (Advanced Biomedical Research, 2016)
Background: The increasing number of mobile phones can physically cause electromagnetic interference (EMI) in medical environments; can also cause errors in immunoassays in laboratories. The ELISA readers are widely used as a useful diagnostic tool for Enzymun colorimetric assay in medicine. The aim of this study was to investigate whether the ELISA reader could be interfered by the exposure to the 900 MHz cell phones in the laboratory. Materials and Methods: Human serum samples were collected from 14 healthy donors (9 women and 5 men) and each sample was divided into four aliquots and was placed into four batches for the in-vitro quantitative determination of human chorionic gonadotropin (hCG). During colorimetric reading of the first, second, and third batches, the ELISA reader (Stat Fax 2100, Awareness Technology, Inc., USA) was exposed to 0.5, 1.0, and 2.0 W exposure of 900 MHz radiation, respectively. For the forth batch (control group), no radiation was applied. All experiments were performed comparing ELISA read out results of the I, II, and III batches with the control batch, using the Wilcoxon test with criterion level of P = 0.050. Results: The final scores in the exposed batches I, II, and III were not statistically significant relative to the control batch (P > 0.05). The results showed that 900 MHz radiation exposure did not alter the ELISA measured levels of hCG hormone in I (P = 0.219), II (P = 0.909), and III (P = 0.056) batches compared to the control batch. Conclusion: This study showed that ELISA reader does not interfere by mobile phone RF radiation at a closed contact (less than 5 cm distance). However, we recommend that medical institutions discuss these issues in the context of their specific use of technologies and frame a policy that is clear and straightforward to guide staff, patients, and visitors.